2017
DOI: 10.1111/jam.13465
|View full text |Cite
|
Sign up to set email alerts
|

Influence of freezing temperatures prior to freeze-drying on viability of yeasts and lactic acid bacteria isolated from wine

Abstract: Freezing temperature to freeze-dry cells is a crucial factor for ensuring good wine yeast and LAB survival. These results are important for appropriately preserving micro-organisms and for improving starter production processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Lyophilization is also a common method of preserving tissue including AM, but viable cells in the tissue are compromised during lyophilization resulting in non-viable tissues. For desiccation-tolerant cells like bacteria and yeast, lyophilization is the current method of choice for long-term ambient storage without loss of cell viability [ 55 , 56 ]. Desiccation-tolerant cells have high concentrations of small carbohydrates (di- and trisaccharides), such as sucrose, maltose, trehalose or raffinose, that protect intracellular molecules and organelles from damage [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lyophilization is also a common method of preserving tissue including AM, but viable cells in the tissue are compromised during lyophilization resulting in non-viable tissues. For desiccation-tolerant cells like bacteria and yeast, lyophilization is the current method of choice for long-term ambient storage without loss of cell viability [ 55 , 56 ]. Desiccation-tolerant cells have high concentrations of small carbohydrates (di- and trisaccharides), such as sucrose, maltose, trehalose or raffinose, that protect intracellular molecules and organelles from damage [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both the cryoprotectants and the nature of kefir culture (free or immobilized cells) had a significant (p < 0.05) effect on cell survival, and a strong (p < 0.05) interaction between the two factors was also observed. Cell immobilization had a negative effect upon the yeast survival rate in most cases (especially cell immobilization on apple pieces [9]), probably due to the longer time required for drying (72 h for immobilized cells on apple pieces in contrast to 24 h in free and immobilized cells on DCM and grape skins), owing to the hydrophilic nature of the immobilization support or because of yeast cells' size and structure [45]. Only cell immobilization on grape skins had a significant (p < 0.05) positive effect on the survival of yeasts/molds when 25% w/v lactose, 10% and 25% v/v glycerol and grape must were used as cryoprotectants.…”
Section: Freeze-drying and Cell Viability Determinationmentioning
confidence: 99%
“…The high viability of the Leuc. lactis CCMA0415 cells could likely be attributed to their peptidoglycan composition, as suggested by Polo et al (2017), who reported the presence of meso-diaminopimelic acid in the cell wall of LAB with a freezing tolerance of −196°C.…”
Section: Re Sults and Discussionmentioning
confidence: 71%